The effect of almond intake on lipid profile: a systematic review and meta-analysis of randomized controlled trials. Issue 5 (15th February 2021) - Asbaghi, Omid; Moodi, Vihan; Hadi, Amir; Eslampour, Elham; Shirinbakhshmasoleh, Mina; Ghaedi, Ehsan; Miraghajani, Maryam
Abstract : A number of clinical trials have examined the effect of almond intake on the lipid profile in recent years; however, the results remain equivocal. Abstract : A number of clinical trials have examined the effect of almond intake on lipid profile in recent years; however, the results remain equivocal. Therefore, the present study aims to summarize and quantitatively examine the available evidence on the effectiveness of almond intake on lipid parameters by employing a systematic review and meta-analytic approach. Online databases including PubMed, Scopus, Embase, and Cochrane Library were searched up to September 2020 for randomized controlled trials that examined the effect of almond intake on lipid profile in adults. Treatment effects were expressed as weighted mean difference (WMD) and the corresponding standard error (SE) in the concentrations of serum lipids. To estimate the overall effect of almond intake, we employed the random-effect model. In total, 27 studies with 36 effect sizes were included in our analysis (1154 cases and 904 control subjects). The meta-analysis revealed that almond intake significantly changed the concentrations of triglycerides (WMD = −6.68 mg dL −1 ; 95% CI: −11.62, −1.75, p = 0.008), total cholesterol (WMD = −4.92 mg dL −1 ; 95% CI: −7.81, −2.03, p = 0.001), and low-density lipoproteins (WMD = −5.65 mg dL −1 ; 95% CI: −8.75, −2.55, p < 0.001); however it did not have a significant effect on high-density lipoprotein (WMD = −0.21 mg dL −1 ; 95% CI: −1.26, 0.84, p = 0.697) levels. Meta-regression analysis indicated a linear relationship between the dose of almond and change in TG (P = 0.021). This meta-analysis concludes that almond intake can significantly reduce lipid parameters. To draw straightforward conclusions regarding generalized recommendations for almond intake for improving lipid profile, there is a need for more well-controlled trials exclusively targeting patients with dyslipidaemia.